Pendidikan Perempuan Tinjauan Konsep Pendidikan Islam dalam Perspektif KH. Abdurrahman Wahid (Gus Dur) - Desfiana Ramdhani Rosalia; Ahmad Fauzi (Universitas Insan Budi Utomo, 2023)
This article examines the perspectives of women within the framework of Islamic education through the lens of prominent individuals. KH is the individual under review in the context of Islamic education. Abdurrahman Wahid (Gus Dur). The objective of this research is to ascertain the viewpoints on women's education in relation to the concept of Islamic education espoused by KH. Abdurrahman Wahid (Gus Dur). A qualitative research methodology is employed in this study, wherein the data are presented through descriptive analysis and structured around a literature review encompassing various discussions. This study underscores the essential elements of the KH. Abdurrahman Wahid's (Gus Dur) perspective on women's education within the framework of Islamic education. The results of this study are based on an analysis of women's education based on a review of Islamic education according to KH. Abdurahman Wahid or Gus Dur can be known to be four parts, namely equality, freedom and justice, and democracy